A novel visible light active rare earth doped CdS nanoparticles decorated reduced graphene oxide sheets for the degradation of cationic dye from wastewater. (January 2022) - Devendran, Pazhanivel; Selvakumar, Duraisamy; Ramadoss, Govindarajan; Sivaramakrishnan, Ramachandran; Alagesan, Thangavel; Jayavel, Ramasamy; Pandian, Kannaiyan
Abstract: A variety of rare earth metals (La, Sm, Nd, Ce, Gd) doped cadmium sulfide (RE-CdS) grafted reduced graphene oxide (G) sheet nanocomposites estimated imperative attention due to their visible light-driven, tunable band gap and high surface to volume ratio were investigated for the photocatalytic degradation of cationic dye from aqueous solution. The formation of wurtzite (hexagonal) crystal structures of cadmium sulfide nanoparticles (NPs) was confirmed by Powder X-ray diffraction spectra and the average crystallite size was determined to be 10 ± 2 nm. HRTEM analysis confirmed the homogeneous distribution of RE-CdS NPs over the G sheets. The photocatalytic behaviour of the RE-CdS decorated G sheets was studied using a textile dye methylene blue (MB) under sunlight. The result indicates that among the various RE-CdS nanocomposites studied, Cerium-cadmium sulfide-reduced graphene oxide (Ce–CdS-G) shows highest MB degradation of 99.0 ± 0.4% within 90 min under sunlight. The result confirms that RE-CdS-G nanocatalyst efficiently accelerates the separation and slows down the recombination rate in photo excited charge carriers. The catalytic activity was retained over 80% of its original value even after four successive runs and the present method can be employed for the large-scale synthesis of RE-CdS-G nanocatalyst. Graphical abstract: Image 1 Highlights: Synthesis of rare earth doped CdS NPs grafted on G sheets by microwave irradiation. RE-CdS-G was investigated for the degradation of MB under direct sunlight. MB degradation of 99.0 ± 0.4% was observed within 90 min using Ce–CdS-G nanocomposites. The degradation of MB using RE-CdS-G followed first order kinetics.